Formation of the Information and Psychological Security System of the Collective Security Treaty Organization - R. S. Vykhodets (Евразийская интеграция: экономика, право, политика, 2023)
The present study is devoted to the analysis of the process of formation at the CS TO level of a system of collective actions to ensure information and psychological security.Aim. To substantiate the relevance of the formation of the information and psychological security system at the CSTO level.Tasks. To identify the information and psychological component in the CSTO collective security strategy, to analyze practical steps at the CSTO level in the field of countering destructive information influence, to determine the regulatory, political and organizational prerequisites for the formation of the CSTO collective information and psychological security system.Methods. In the study, the author used general scientific methods of analysis and synthesis. Special methods were also applied: comparative analysis, informational approach, neoinstitutional approach, critical discourse analysis and content analysis.Results. The study showed that the issues of countering destructive information influence are given considerable attention in the CSTO strategic documents and a number of model laws adopted by the CSTO Parliamentary Assembly, in addition, the relevance of these issues is emphasized in joint statements following meetings in various formats.The term “information and psychological security” is not used in official documents of the CSTO. Currently, issues related to the field of information and psychological security are conceptually included in the general list of tasks in the field of information security. Special attention is paid to countering malicious ideological and psychological influence on the Internet.Today, the main subjects of practical activity in the field of ensuring the information security of the CSTO, including in the field of countering destructive information influence, are the power structures of the member states implementing special operations in the information space. However, taking into account the degree of penetration of Internet technologies and media messages of citizens of the CSTO member states, the effectiveness of such events is unlikely to be able to qualitatively change the situation. That is why it is necessary to create an integrated system of information and psychological security at the CSTO level.Conclusions. In modern conditions of global competition, which have sharply escalated after the start of Russia’s Special Military Operation on the territory of Ukraine in February 2022, the formation of a unified system of collective actions at the CSTO level, providing, on the one hand, reliable protection from targeted malicious influence in the information environment, and on the other, forming a positive ideological and informational agenda of the community, is of particular relevance the historical path of development, the unity of economic and geopolitical tasks, the solution of which will make it possible to implement national development priorities as effectively as possible and ensure the collective security of the participating countries in the modern world.